Glider observations in the Western Mediterranean Sea: their assimilation and impact assessment using four analysis and forecasting systems - Aydogdu, Ali; Escudier, Romain; Hernandez-Lasheras, Jaime; Amadio, Carolina; Pistoia, Jenny; Zarokanellos, Nikolaos D.; Cossarini, Gianpiero; Remy, Elisabeth; Mourre, Baptiste (Frontiers in Marine Science, 2025)
We present an impact assessment of temperature and salinity glider observations on physical analysis and forecasting systems operating in the Western Mediterranean Sea through one-year-long coordinated experiments. A unique set of glider observations including data from several endurance lines provided by different institutions is assimilated in the three systems. Results are compared against an assimilation-free run and an assimilative-run that with each systems’ default configuration. Moreover, an additional biogeochemical analysis system is forced by two physical runs with and without the assimilation of glider observations. First of all, we demonstrate that glider data assimilation has an overall positive impact on the state estimation of the Western Mediterranean Sea, independently of the system employed and the pre-processing approach used to ingest the glider measurements. Secondly, we show that it helps improve the representation of mesoscale structures, in particular the location and size of an intense anticyclonic eddy observed in the Balearic Sea. Thirdly, the geostrophic currents and transport of Winter Intermediate Water in the Ibiza Channel are also improved. Finally, the adjustment of the mixing after glider data assimilation in the physical system translated to a better estimate of chlorophyll distribution in the upper layer of the biogeochemical system. Leading to the same order of magnitude of improvement in the different forecasting systems, this intercomparison exercise provides robustness of the obtained impact assessment estimates. It also allows us to identify relative strengths and weaknesses of these systems, which are useful to identify future ways of improvement. Overall, this study demonstrates the value of repeated glider observations collected along endurance lines for regional ocean prediction.